2015
DOI: 10.1002/term.2022
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative tracking of passage and 3D culture effects on chondrocyte and fibrochondrocyte gene expression

Abstract: Success in cartilage and fibrocartilage tissue engineering relies heavily on using an appropriate cell source. Many different cell sources have been identified, including primary and stem cells, along with experimental strategies to obtain the required number of cells or to induce chondrogenesis. However, no definitive method exists to quantitatively evaluate the similarity of the resulting cell phenotypes to those of the native cells between candidate strategies. In this study, we develop an integrative appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…In addition, in this study, fibrochondrocytes from juvenile bovine menisci were employed. It has been demonstrated that fibrochondrocytes from adult bovids show a higher ratio of collagen type I to II gene expression compared to those cells from juvenile bovids . The effects of growth factors on fibrochondrocytes from either juvenile or adult bovids also vary .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in this study, fibrochondrocytes from juvenile bovine menisci were employed. It has been demonstrated that fibrochondrocytes from adult bovids show a higher ratio of collagen type I to II gene expression compared to those cells from juvenile bovids . The effects of growth factors on fibrochondrocytes from either juvenile or adult bovids also vary .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that fibrochondrocytes from adult bovids show a higher ratio of collagen type I to II gene expression compared to those cells from juvenile bovids. 82 The effects of growth factors on fibrochondrocytes from either juvenile or adult bovids also vary. 19 With regard to the zonal difference, it has been shown that cells from the inner zone produce more proteoglycans than those cells from the outer zone.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Although meniscal fibrochondrocytes might seem to be an obvious choice for engineering the meniscus, co-culturing these cells with others might be required to achieve the best results. Similar to chondrocytes, meniscal fibrochondrocytes dedifferentiate when expanded 135 , a fact that has led to the investigation of MSCs from the bone marrow 136 , synovium 137 and adipose tissue as alternative cell sources 138 . In a 2017 study,…”
Section: Engineering Meniscimentioning
confidence: 99%
“…While scaffolds are beneficial due to their ability to incorporate growth factors and their initial mechanical stability, they also indicate recapitulation of the mechanical and biochemical architecture of the native meniscus, with matched stiffness and ingredient gradients (Higashioka, et al, 2014;Steele, et al, 2014;Zhu, et al, 2018;Zitnay, et al, 2018). Notably, when engineering menisci for regeneration, although an obvious choice for cell source might be fibrochondrocytes, regeneration effects are best when fibrochondrocytes are cocultured with other cell subsets (Hadidi, et al, 2016;Koh, et al, 2017;Son and Levenston, 2017;Sasaki, et al, 2018;Xie, et al, 2018). Zhang C. H. et al (2018) used a pre-mechanically stimulated poly (ε-caprolactone) (PCL) scaffold, cocultured with rabbit bone marrow stem cells, for meniscus replacement and found that the pretreated scaffold was a better choice for inducing tissue regeneration (Figure 2).…”
Section: Tissue Engineering Strategies For Meniscus Regenerationmentioning
confidence: 99%